2018
DOI: 10.1002/smll.201704221
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong‐Discharge‐Time Biobattery Based on Immobilized Enzymes in Bilayer Rolled‐Up Enzymatic Nanomembranes

Abstract: Glucose biofuel cells (GBFCs) are highly promising power sources for implantable biomedical and consumer electronics because they provide a high energy density and safety. However, it remains a great challenge to combine their high power density with reliable long-term stability. In this study, a novel GBFC design based on the enzyme biocatalysts glucose dehydrogenase, diaphorase, and bilirubin oxidase immobilized in rolled-up titanium nanomembranes is reported. The setup delivers a maximum areal power density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…As a result, in recent years more efforts have been focused on renewable sources of electricity, which is any form of energy generated from natural resources (e.g. solar, wind, and biofuels) 4 , 5 . However, the instable productivity of these energy types remains a big challenge in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in recent years more efforts have been focused on renewable sources of electricity, which is any form of energy generated from natural resources (e.g. solar, wind, and biofuels) 4 , 5 . However, the instable productivity of these energy types remains a big challenge in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…The footprint per tube was as small as 1.5 × 10 −4 cm 2 and the power density as high as 257 mW cm −2 , which is three orders of magnitude higher than conventional microsized methanol fuel cells. Liu et al reported a novel glucose biobattery based on the enzyme biocatalysts glucose dehydrogenase, diaphorase, and bilirubin oxidase immobilized in rolled‐up titanium nanomembranes (Figure e) . The device delivers a maximum areal power density of about 3.7 mW cm −2 and a stable power output of about 0.8 mW cm −2 .…”
Section: State‐of‐the‐art Self‐assembled Microelectronic Devicesmentioning
confidence: 99%
“…Both mechanical (Adapted with permission . Copyright 2008, Wiley‐VCH) and electrical energy can be obtained in different ways through chemical reactions, biological processes such as in biobatteries (Adapted with permission . Copyright 2018, Wiley‐VCH), or by photovoltaic (Adapted with permission .…”
Section: Self‐assembled Microelectronic Systemsmentioning
confidence: 99%
See 2 more Smart Citations